The clinical study to evaluate the Rasayana effect of Bharangi Guda in Post-Covid Subjects - Research Article - Roopa N; SN Belavadi (Journal of Ayurveda and Integrated Medical Sciences, 2025)
In COVID-19, long term intake of Antivirals, Antibiotics, Antimicrobials, Corticosteroids and ventilator exposure leads to ill effect in individual. Such as Fatigue, Weight loss, Weakness, Intermittent raise in Temperature, Headaches, Myalgias etc. are signs and symptoms noted in after effect of COVID-19. It is necessary to combat Post-covid signs and symptoms in patients and restore the normalcy of body functions or to build their immune system. Rasayana an Ayurvedic rejuvenation therapy which helps in maintenance and promotion of health. It means nutrition at all levels from macro to micro cellular levels. Replenishes from the vital fluids of body; boost the Ojas (immune system), thus keeping away from diseases. In the study; Naimittika Rasayana (consequent to diseases), Bharangi Guda which is indicated in Pranavaha Sroto Vikara like Swasa (asthma), Kasa (cough), Jwara (fever) etc. Ingredients like Bharangi, Dashamoola, Harithaki, Guda, Trikatu, Trijatha, Yava. Actions like Antispasmodic, Anti-asthmatic, Carminative, Antihistaminic principle, Tonic and refrigerant. Active principles like Saponin, D-mannitol, Tanin etc. Study design is Simple Randomized Clinical Study. Total 30 post-COVID patients shows highly significant in subjective parameters and significant and not-significant in objective parameters.